The clinical effects of combining postural exercises with chest physiotherapy in cystic fibrosis: A single-blind, randomized-controlled trial - KARADAĞ SAYGI, NAİME EVRİM; KENİŞ COŞKUN, ÖZGE (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2021)
Objectives: This study aims to investigate the effects of postural exercises as an adjunct to chest physiotherapy program on respiratory function, exercise tolerance, quality of life (QoL), and postural stability in patients with cystic fibrosis (CF). Patients and methods: In this single-blind, randomized-controlled trial, 19 pediatric CF patients (11 males, 8 females; mean age:9.36 years; range, 6 to 14 years) were randomly allocated to chest physiotherapy and postural exercise program (Group 1, n=10) or chest physiotherapy program alone (Group 2, n=9) between March 2017 and October 2017. Respiratory functions were assessed with pulmonary function tests, whereas exercise tolerance with the Modified Shuttle Test (MST), quality of life with the Cystic Fibrosis Questionnaire-Revised Child Version (CFQR), and postural stability with the Limits of Stability Test (LOS). All tests were performed before treatment and six weeks, three months, and six months after treatment. Results: Respiratory functions were improved in both groups; however, these changes were not statistically significant. The MST increased after treatment in both groups (p<0.001 and p=0.003 respectively), without a significant difference between the groups. Emotional function and treatment difficulties subdomains in CFQR were significantly increased only in the group with postural exercises (p<0.05). Conclusion: The postural exercise program in addition to chest physiotherapy in pediatric CF patients whose postural changes were not taken place did not cause significant changes in respiratory function, exercise tolerance, and postural stability; however, it affected the emotional state well and improved the compliance with the treatment.
Keywords: Chest physiotherapy; cystic fibrosis; postural exercises; SHUTTLE TEST-PERFORMANCE; LUNG-FUNCTION; CHILDREN; ADOLESCENTS; ADULTS